ANALYSIS OF DETERMINATION OF TRY OUT MATHEMATICS SKILLS OF STUDENTS IN IPA 1 SMA N 1 KECAMATAN WITH CLUSTERING METHODS - MEANS - Sri Tria Siska; Rahayu Mayang Sari (LLDIKTI Wilayah X, 2020)
In this study aims to analyze the determination of the ability of TRY OUT Mathematics students majoring in Natural Sciences in SMA N.1 Kecamatan to get an information that is useful for schools in determining students based on their grades. In processing these data we use data mining with the K-Means Algorithm Clustering Method. Data Mining is extracting information from a large amount of data. The information that was obtained was in the form of groups of students with high grades, medium grades and low grades. The test that we do uses the existing application, RapidMiner, so that it can be determined by the desired student clusters